UTILIZATION OF OIL PALM EMPTY FRUIT BUNCHES AS MULCH IN COMMUNITY OWNED OIL PALM PLANTATIONS (CASE STUDY IN SIMARDONA VILLAGE, NORTH SUMATRA) - Annisa Fitri Harahap; Muslikhin Hidayat; Suhanan Suhanan (ASEAN Journal of Systems Engineering, 2021)
Solid Waste Oil Palm Empty Fruit Bunches have high nutrients, which significantly determine oil palm growth rate and production. Each nutrient has its role and can show specific symptoms in plants if their availability in the soil is very lacking. Dry oil palm land and the difficulty of procuring chemical fertilizers for the community that owns oil palm plantations in Simardona Village are expected to be overcome by the use of OPEFB. Utilization of Oil Palm Empty Bunches as Mulch was done manually in 4 research scenarios. Scenario 1 uses 2 kg of chemical fertilizers plus 250 kg of OPEFB, scenario 2 uses 2 kg of chemical fertilizers plus 300 kg of OPEFB, scenario 3 uses 2 kg of chemical fertilizers plus 350 kg of OPEFB, and scenario 4 uses 2 kg of chemical fertilizers plus 400 kg of OPEFB.The results obtained are that the humidity or moisture has increased from a value of 1 to 4. Therefore, it can be seen that the effect obtained from the use of more OPEFB makes the humidity higher. The calculation of the total cost of using OPOPEFB as mulch is obtained from the sum of the price of chemical fertilizers, the price of OPOPEFB, and workers' wages. The total cost after utilization of TKKS is IDR854,000.00. The total cost before using TKKS was IDR441,600,000. The difference in costs before and after the utilization of TKKS is IDR412,400.00, an increase in costs of 48%. The cost of using TKKS is higher than before using TKKS. The total harvest obtained before the use of OPEFB is 2,000 kg or IDR4,900,000. Meanwhile, after using OPEFB, the total yield obtained was 2,700 kg or IDR6,615,000. Production income increased by 26%.